2014
DOI: 10.2903/j.efsa.2014.3845
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Dietary Reference Values for chromium

Abstract: Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies (NDA) considered the evidence for setting Dietary Reference Values for chromium. Trivalent chromium (Cr(III)) has been postulated to be necessary for the efficacy of insulin in regulating the metabolism of carbohydrates, lipids and proteins. However, the mechanism(s) for these roles and the essential function of Cr(III) in metabolism have not been substantiated. The criteria for the essentiality of a trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(37 citation statements)
references
References 84 publications
1
36
0
Order By: Relevance
“…For Cr 3+ , a possible essential trace element for humans, a TDI of 300 μg kg -1 b.w. has been established, while no TDI has been established for toxic Cr 6+ , and no maximum levels for Cr in food at the EU level are currently established (42,43). EFSA estimated dietary exposure to Cr 3+ in the European population between 0.6 and 5.9 μg kg -1 b.w.…”
Section: Discussionmentioning
confidence: 99%
“…For Cr 3+ , a possible essential trace element for humans, a TDI of 300 μg kg -1 b.w. has been established, while no TDI has been established for toxic Cr 6+ , and no maximum levels for Cr in food at the EU level are currently established (42,43). EFSA estimated dietary exposure to Cr 3+ in the European population between 0.6 and 5.9 μg kg -1 b.w.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest Cr concentration (3 ± 0.5 mg kg -1 ) per dry mass in fenugreek seed was recorded at the Korem site. The AI for Cr is 35 μg per day and 25 μg per day, for young men and young women, respectively (EFSA, 2014). In addition to the above, the ESADDIs for Cr for adults is 50-200 μg per day (WARDLAW, 1997).…”
Section: Levels Of Essential and Toxic Metals In Fenugreek Seeds (Trimentioning
confidence: 99%
“…In its Scientific Opinion on dietary reference values (DRVs) for chromium, the NDA Panel concluded that the essential function of chromium (as Cr(III)) in metabolism has not been substantiated and no average requirement (AR) and population reference intake (PRI) for chromium can be defined. The Panel also concluded that there was no evidence of beneficial effects associated with chromium intake in healthy subjects and, therefore, the setting of an adequate intake (AI) for chromium was also not appropriate (EFSA NDA Panel, 2014).…”
Section: Nutritional Informationmentioning
confidence: 99%